Утвердження народовладного концепту у державно-правових поглядах та політичній діяльності Костя Левицького - Сворак, С. Д.; Svorak, S. D. (Право і безпека. - 2013. - № 2 (49). - С. 50-55, 2013)
Проаналізовано транформацію народовладного концепту у державно-правових поглядах та політико-правовій діяльності президента ЗУНР доктора права Костя Левицького, розкрито етапи становлення його державницького світогляду, віхи політичної діяльності, формування національно-правової свідомості у період становлення та модернізації українського національно-визвольного руху, утвердження національної ідеї серед широких верст населення Західної України.

Transformation of democratic concept in state and legal views and political and legal activity of the President of Western Ukrainian People’s Republic, Doctor of Law Kost Levitskiy is analyzed; stages of his state outlook, milestones of political activity, formation of national and legal awareness in the period of establishing and modernization of Ukrainian national and liberation movement, establishment of the national idea among wide sections of Western Ukraine’s population are disclosed. The author stresses that K. Levitskiy, has joined to the fight for the better fate of the people while his high school years, under the influence of Ukrainian patriots and works of T. Shevchenko, and has become an active member of student societies, «Prosvita» that made him a prominent feature in the social and cultural life of Galychyna. It is outlined in the article that K. Levytskiy, as the head of the Main Ukrainian Rada, at the time of the First World War, made a proposition to create Ukrainian Legion in Galychyna, namely national military unit – Legion of Ukrainian Sich Riflemen. He could convince the government and Austria-Hungary military men in democracy and loyalty of Ukrainians to power. The author stressed that he especially needed lawyer’s experience while parliamentary activities in the Austrian parliament and Galytskiy Seym. None of the laws was not passed without his rigorous analysis and in his parliamentary speeches he defended the right of Ukrainian population of Eastern Galychyna to increase the number of Ukrainian primary and secondary schools, Ukrainian budgetary financing of social programs in the provinces and districts of Eastern Galychyna, etc. Describing the activity of K. Levitskiy directed on state development in the period of Western Ukrainian People’s Republic, the author stresses his participation in the formation of democracy concept, while writing and structuring the draft of the Constitution known as «The Principles of Government System in the Republic of Galychyna», where democracy is the cornerstone for building the future of Ukrainian national state.

Проанализирована трансформация народовластного концепта в государственно-правовых взглядах и политико-правовой деятельности президента ЗУНР доктора права Костя Левицкого, раскрыты этапы становления его государственного мировоззрения, вехи политической деятельности, формирование национально-правового сознания в период становления и модернизации украинского национально-освободительного движения, утверждения национальной идеи среди широких слоев населения Западной Украины.
Establishment of democratic concept in state and legal views and political activity of K. Levitskiy
Keywords: демократія; національно-демократична революція; державний апарат ЗУНР; публічна адміністрація; Левицький, К.; democracy; national and democratic revolution; state administration of Western Ukrainian People’s Republic; public administration; Levitskyi, K.; демократия; национально-демократическая революция; государственный аппарат ЗУНР; публичная администрация; Левицкий, К.